2023
DOI: 10.1186/s12885-023-10787-5
|View full text |Cite
|
Sign up to set email alerts
|

Time trends in survival and causes of death in multiple myeloma: a population-based study from Germany

Abstract: Background Steady evolution of therapies has improved prognosis of patients with multiple myeloma (MM) over the past two decades. Yet, knowledge about survival trends and causes of death in MM might play a crucial role in long-term management of this patient collective. Here, we investigate time trends in myeloma-specific survival at the population level over two decades and analyse causes of death in times of prolonged survival. Methods Age-standa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 35 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…The five-year survival rate of multiple myeloma is around 57%, and the prognosis has increased due to therapeutic advances [ 6 ]. Multiple myeloma should be classified into high- or standard-risk groups, and proper treatment regimens should be initiated in such a way that future treatment is unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…The five-year survival rate of multiple myeloma is around 57%, and the prognosis has increased due to therapeutic advances [ 6 ]. Multiple myeloma should be classified into high- or standard-risk groups, and proper treatment regimens should be initiated in such a way that future treatment is unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment decision is currently based on age, performance status and risk stratification ( 7 ). Age-standardized five-year survival has increased from 41% to 69% for patients under 69 years old and from 23% to 47% for patients between 70 and 79 years old ( 8 ). Despite significant progress, MM remains incurable and inevitably all patients will experience relapses and eventually develop refractory disease.…”
Section: Introductionmentioning
confidence: 99%
“…Much progress has been made in the past 20 years. Real-world studies showed that the 5-year survival rate increased from 37 to 62% (years 2000–2019) in a German population [ 2 ] and increased from 27 to 47% (years 1994–2016) in a Spanish population [ 3 ]. These successes can be attributed to the development of more effective therapies; however, patients will eventually develop relapsed and/or refractory MM (RRMM) and require further therapy [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%